PENGARUH PERSEPSI MASYARAKAT BATAM TENTANG BANK SYARIAH TERHADAP MINAT MENGGUNAKAN PRODUK BANK SYARIAH - Imran Imran; Bambang Hendrawan (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
This research examines the influence of society’s perception about sharia bank toward intends to use sharia bank products. The data collection technique was a field survey that using questionnaire to the sample respondents. Sampling method used is accidental sampling method with 100 selected people by accidently. The data analysis method uses multiple linear regression model. The result of this research indicate that people perception about bank sharia in banking system with interest, profit sharing system characteristics and sharia product knowledge, simultaneously have positive significant effect toward intends to use sharia product. Partially, only perception from knowledge of product variable has no influence toward society intends to Sharia bank products. Its means the better understanding about the no-interest banking system and also about profit sharing system as a basis for sharia bank practices, will increase society’s intends to use sharia products. Meanwhile, there is no effect for society perception whether they have a better or less knowledge of sharia bank products